If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4 = 6x + 6 Reorder the terms: -4 + 2y = 6x + 6 Reorder the terms: -4 + 2y = 6 + 6x Solving -4 + 2y = 6 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2y = 6 + 4 + 6x Combine like terms: -4 + 4 = 0 0 + 2y = 6 + 4 + 6x 2y = 6 + 4 + 6x Combine like terms: 6 + 4 = 10 2y = 10 + 6x Divide each side by '2'. y = 5 + 3x Simplifying y = 5 + 3x
| x+48((yx^2)+-2)=20 | | 16+x^2=64 | | (61)+(75)+(4x+3)+(17x-3)+(4x+5)=360 | | 5x-8x=3-9 | | 13x=108 | | 25+x^2=64 | | 61+75+(4x+3)+(17x-3)+(4x+5)=360 | | 12-x=0.3(x+1) | | 4nut=5dez | | 1/7(4y+5)=4+1/5(y+4) | | 61+75+(4x+3)+(17x-3)+(4x+5)=180 | | 61+75+(4x+5)+(17x-3)+(4x+5)=180 | | b-12b-64=0 | | 8b^2-5b-10= | | 16+x^2=36 | | 10=8t-6t | | 2ln(-x)16x=3 | | 5(140y+175)=140+175(35y+140) | | (45x+5)=(46x+2) | | 6x+6=x-2 | | w=5y-x | | x^2=2-66 | | w=5y-xfory | | 0.60x+0.60(40)=0.30(38) | | (11x-6)+(7x+5)+55=180 | | 2(3x+1)+6(x-2)= | | 0.4(7c+5)=3.1c-2.2 | | (65+59)+9x+2=180 | | 11x+17=180 | | 300-5x=-150 | | 24x+2=50 | | 4-2/3x=-6 |